1997
DOI: 10.1046/j.1365-3040.1997.d01-8.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between water stress, sun‐shade acclimation, heat tolerance and photoinhibition in the sclerophyll Heteromeles arbutifolia

Abstract: Gas exchange and chlorophyll fluorescence techniques were used to evaluate the acclimation capacity of the schlerophyll shrub Heteromeles arbutifolia M. Roem. to the multiple co-occurring summer stresses of the California chaparral. We examined the influence of water, heat and high light stresses on the carhon gain and survival of sun and shade seedlings via a factorial experiment involving a slow drying cycle applied to plants grown outdoors during the summer. The photochemical efficiency of PSII exhibited a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
272
2
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(290 citation statements)
references
References 41 publications
(49 reference statements)
13
272
2
3
Order By: Relevance
“…They suggested that the dust may act directly on the guard cells, though the mechanisms for this effect remain uncertain till date. Simultaneous depression in CO 2 uptake and PS II photochemical efficiency (Table 4), caused by CFA, have been reported for several other plant species [52,53] .…”
Section: Discussionsupporting
confidence: 54%
“…They suggested that the dust may act directly on the guard cells, though the mechanisms for this effect remain uncertain till date. Simultaneous depression in CO 2 uptake and PS II photochemical efficiency (Table 4), caused by CFA, have been reported for several other plant species [52,53] .…”
Section: Discussionsupporting
confidence: 54%
“…Leaf temperature, water status and stomatal opening are interconnected in a complex manner (Valladares and Pearcy, 1997;Feller, 2006;Reynolds-Henne et al, 2010;Feller and Vaseva, 2014;Teskey et al, 2015). Increased abscisic acid levels cause closure of stomates and reduce leaf cooling by transpiration.…”
Section: Photosynthetically Active Leaf Areamentioning
confidence: 99%
“…As a measure of abiotic stress, we used the Fv/Fm ratio (Maximum Quantum Efficiency of Photosystem II). This parameter is accepted and widely used as reliable diagnostic indicator of plant photochemical performance (He et al 1996;Valladares and Pearcy 1997;Maxwell and Johnson 2000;Kalaji and Guo 2008). ANOVA and Tukey's tests were applied to the resulting data.…”
Section: Chlorophyll Fluorescencementioning
confidence: 99%